Change of turbidity maximum in Yangtze Estuary after construction of the Three Gorges Dam. (1st April 2023) - Zhao, Leihua; Xin, Pei; Cheng, Haifeng; Chu, Ao
Abstract: Estuarine turbidity maxima (ETMs) are of sedimentological, geomorphological and ecological significance. In this study, a well-validated and process-based sediment transport model was used to investigate the response of ETM dynamics in the Yangtze Estuary (YE) to construction of the Three Gorges Dam (TGD) and morphological evolution of the YE. The model results demonstrated that the ETM dynamics change in the upper estuary was controlled by the TGD construction. After the TGD construction, the ETM area decreased by 22% (from 1116 to 874 km 2 ) and the ETM center location moved landward 7 km during the flood season. The estuarine morphological evolution played a key role in the ETM dynamics change of the mid-lower estuary. The ETM area decreased by 55% (from 1478 to 658 km 2 ) and 15% (from 658 to 562 km 2 ) due to the estuarine morphological evolution from 1998 to 2010 and from 2010 to 2018, respectively. Meanwhile, the ETM center location moved landward 38 km and 7 km during the periods 1998–2010 and 2010–2018, respectively. Overall, both the TGD construction and estuarine morphological evolution induced decreased suspended sediment concentrations in the estuary. Furthermore, the effect of TGD construction was dominant in the upper estuary, whereas the effect of estuarine morphological evolution became dominant in the mid-lower estuary. These findings provide implications for management of the YE and other similar estuaries. Highlights: Estuarine turbidity maximum (ETM) decreased by 22% and moved landward 7 km after Three Gorges Dam (TGD) construction. Estuarine morphological evolution induced ETM to decrease by 15–55% and move landward 7–38 km. TGD construction and morphological evolution dominated ETM changes in upper and mid-lower estuaries, respectively.